Nikah Siri In Maqāṣid al-Sharī'ah Review: A Critical Study of the Urgency of Marriage Registration in Islam - Efendi, Zulfan; Waid, Abdul (El-Sirry: Jurnal Hukum Islam dan Sosial, 2025)
This study examines the status of serial marriage and the urgency of marriage registration in Islam using the Maqāṣid al-Syarī'ah approach. This research is a normative legal research with a qualitative approach, which uses conceptual and legislative approaches. Data was obtained through literature studies on Islamic legal sources, ushul fiqh rules, and laws and regulations in Indonesia, especially Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law. The results of the study show that the practice of serial marriage that still occurs in society has the potential to cause various negative impacts, especially for wives and children, such as the absence of legal certainty, difficulties in fulfilling inheritance rights, and weak protection of family rights. In the perspective  of Maqāṣid al-Syarī'ah which is oriented towards the benefit and prevention of harm, nikah siri is seen as a practice that causes harm. Based on the rules of dar'u al-mafāsid muqaddam 'alā jalb al-maṣāliḥ, marriage registration is positioned as an urgent need (ḍarūriyyāt) to protect offspring (ḥifẓ al-nasl) and property (ḥifẓ al-māl). This study concludes that marriage registration in KUA or Civil Registry is an obligation in every marriage. State policies that require marriage registration are considered to be in line with the purpose of Islamic law in realizing the benefits and protection of citizens' rights. Thus, in the current context, nikah siri can be considered invalid because it is contrary to the principle of prevention of damage.